Impact of IoT in Banking Processes - Ramani Jaydeep R.; Jayesh N. Zalavadia (International Journal of Mobile Computing Technology, 2023)
The Internet of things (IoT) represents the next phase of the digital world that is expanding rapidly and transforming the lives of customers. While the Internet does not usually extend beyond the electronic world, connected objects represent the extension of internet of things and places with the adaptations of IOT in personalized services like online banking. Contactless payment technologies are demanding convenient and personalized services in IoT base banking application which provide high quality fast response to their customer anywhere, anytime. Customers are always expecting the highest level of digital security from their banks where machine to machine connectivity helps the organization to collect mass data and exchange of data with the help of sensors and numerous opportunities in banking sector. Banks always need to convert IoT into profitable data which increases their market share and gives better services to their customers. In this study, we would like to find some of the frauds in the banking sector and proposed framework.
Keywords: Cloud; Internet; Internet of things (IoT); device; sensor; technologies